(untitled) (Research, Society and Development, 2023)
Objective: to analyze the knowledge of intensive care nurses in relation to the care provided to patients undergoing coronary angiography. Method: this is a descriptive-exploratory field research, with a qualitative approach, carried out between June and August 2022 in 2 Adult Intensive Care Units of a Public Hospital in the city of São Paulo, using Google Forms©. Results: the research carried out interviewed a total of 21 nurses, a number corresponding to 100% of the professionals working in the day shift. The average of correct answers for the closed questions was 60%, in relation to the essay questions the answers were significant. Discussion: it was noticed that nurses, despite knowing about the subject studied, need to be updated, as well as participating in permanent education on coronary angiography. Conclusion: it is extremely important that the nurse as a professional develops safe and effective means of care and seeks to improve with nursing care methodologies, seeking to base himself on knowledge, aiming to promote a holistic, humanized and resolute care.